In Situ Study of Zinc Peroxide Decomposition to Zinc Oxide by X‐Ray Absorption Spectroscopy and Reverse Monte Carlo Simulations. Issue 9 (29th March 2022) - Kuzmin, Alexei; Pudza, Inga; Klementiev, Konstantin
Abstract : The Zn K‐edge X‐ray absorption spectroscopy is used to investigate in situ the decomposition of zinc peroxide ( ZnO 2 ) to zinc oxide (ZnO). Principal component and linear combination analyses of the extended X‐ray absorption fine structure (EXAFS) spectra are employed to identify the phase composition of the oxide upon heating to 900 °C. Only the ZnO 2 phase is found up to 180 °C, whereas only the nanocrystalline ZnO phase is occurring above 250 °C. Detailed structural information on the temperature dependence of the local environment of zinc atoms is obtained using the reverse Monte Carlo (RMC) simulations. A strong increase of disorder is found upon approaching the decomposition temperature, evidenced by the broadening of Zn–O and Zn–Zn pair distribution functions (PDFs) and related mean‐square relative displacements. Abstract : In situ Zn K‐edge X‐ray absorption spectroscopy combined with the reverse Monte Carlo (RMC) simulations is used to study the decomposition process of ZnO 2 to ZnO. The variations in the local environment around zinc atoms are discussed based on the analysis of pair atomic and bond angle distribution functions (BADFs).